Organocatalytic Friedel–Crafts Alkylation/Lactonization Reaction of Naphthols with 3‐Trifluoroethylidene Oxindoles: The Asymmetric Synthesis of Dihydrocoumarins. Issue 1 (30th November 2016) - Zhao, Yun‐Long; Lou, Qin‐Xin; Wang, Long‐Sheng; Hu, Wen‐Hui; Zhao, Jun‐Ling
Abstract: Naphthols and 3‐trifluoroethylidene oxindoles were found to undergo an asymmetric Friedel–Crafts alkylation/lactonization reaction, catalyzed by only 2.5 mol % of a quinine‐derived squaramide catalyst, to afford the corresponding α‐aryl‐β‐trifluoromethyl dihydrocoumarin derivatives in high yields (up to 99 %) with excellent enantio‐ and diastereoselectivities (up to 98 % ee, >20:1 d.r.). Importantly, the lactonization proceeded by nucleophilic attack of the naphthol hydroxy group at the amide motif of the oxindoles under mild reaction conditions. This protocol represents a new strategy for the formation of dihydrocoumarins by an efficient intramolecular amide C−N bond‐cleavage and esterification process. Abstract : Crafty : A new [3+3] strategy has been developed for the organocatalytic enantioselective synthesis of α‐aryl‐β‐trifluoromethyl dihydrocoumarins. The Friedel–Crafts addition of naphthols to 3‐trifluoroethylidene oxindoles and subsequent esterification, through cleavage of the amide C−N bond by the hydroxy group of the naphthol, furnished the corresponding dihydrocoumarin products in high yields and excellent enantio‐ and diastereoselectivities.